(untitled) (Texas Journal of Engineering and Technology, 2025)
The paper presents the results of the development of a 3 kW inverter design for solar and wind mini power plants used for the national economy and industry, as well as the design and manufacture of a pilot batch of solar inverters designed for use as part of photovoltaic or wind power plants.